Off-farm employment and the transforming rural non-farm economy around Yangon - Htun, Aung (Michigan State University, 2018)
This brief focuses on the characteristics of off-farm employment in agriculture and aquaculture clusters, and on gendered differences in employment opportunities and wage rates. It also presents evidence of transformation in the rural non-farm economy in both clusters.